2015
DOI: 10.1007/s00340-015-6186-x
|View full text |Cite
|
Sign up to set email alerts
|

Periodic femtosecond filamentation in birefringent media

Abstract: phenomenon of multiple refocusing [5]. Up to three peaks of on-axis luminescence intensity were observed when the authors of [6] focused a femtosecond laser pulse into an isotropic fused silica sample with a high-NA objective. Multiple irregular refocusing of tightly focused femtosecond laser pulse, with the distance between the refocusing maxima varying from 20 to 40 μm, was observed inside fused silica in [7]. The phenomenon was associated with the focal spot extension along the propagation axis due to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…The periodic structures in Mid-IR filament observed in isotropic LiF have a quite another origin than those reported beforehand under an investigation of filamentation in different media. The observed behavior is opposite to a periodic filamentation of laser femtosecond pulses observed in recent experiments with birefringent crystals, which is caused by the periodic change in the polarization of the pulse travelling in birefringent medium in combination with the cross-sectional difference in multiphoton absorption for the linear and circular polarizations [22]. A period of a single filament structure in these experiments increased with the excitation pulse wavelength increasing in contrast to our measurements with isotropic crystal LiF.…”
Section: Doicontrasting
confidence: 99%
“…The periodic structures in Mid-IR filament observed in isotropic LiF have a quite another origin than those reported beforehand under an investigation of filamentation in different media. The observed behavior is opposite to a periodic filamentation of laser femtosecond pulses observed in recent experiments with birefringent crystals, which is caused by the periodic change in the polarization of the pulse travelling in birefringent medium in combination with the cross-sectional difference in multiphoton absorption for the linear and circular polarizations [22]. A period of a single filament structure in these experiments increased with the excitation pulse wavelength increasing in contrast to our measurements with isotropic crystal LiF.…”
Section: Doicontrasting
confidence: 99%
“…1. The same cycle repeats with a period of 101 m in sapphire and 90 m in quartz: as soon as the phase incursion between the ordinary and extraordinary rays becomes equal to 2 , where is an integer number [11]. Therefore, in what follows, we will discuss only the circular input polarization.…”
Section: Experimental Results and Their Discussionmentioning
confidence: 99%
“…Similar researches can provide information about such slightly studied phenomena that accompany the filamentation as, e.g., the CE generation. A periodic filamentation phenomenon, which was experimentally observed in sapphire and crystalline quartz [11], became another new effect revealed in the recent years. The physical origin of the observed periodicity consists in the cyclic transformation of the polarization state of a light pulse at its propagation in a birefringent medium owing to the incursion of the phase difference between the ordinary and extraordinary rays.…”
Section: Introductionmentioning
confidence: 90%
“…The temporal width of the autocorrelation function of compressed pulses, = 90 fs, is obtained, which corresponds to the 63-fs duration of the pulse at FWHM. It was shown that the physical cause for the temporal compression is the power dependence of the selffocusing distance, which is described by a Marburger formula [7]. Thus, the laser pulse compressed two and a half times was obtained.…”
Section: Early Studiesmentioning
confidence: 97%
“…Earlier, we recorded several spectacular phenomena accompanying the formation of fs filaments in transparent Kerr media such as the temporal self-compression of a fs pulse in filaments [3], phase-dependent repulsive and attractive interactions of two intersecting fs filaments [4][5][6], longitudinal periodicity, which appears in the luminescence of an axial plasma column of filaments in anisotropic crystal media [7].…”
Section: Early Studiesmentioning
confidence: 99%